2013
DOI: 10.2478/s11535-013-0238-1
|View full text |Cite
|
Sign up to set email alerts
|

Short term exposure of Lemna minor and Lemna gibba to mercury, cadmium and chromium

Abstract: The effects of mercury (Hg), cadmium (Cd) and chromium (Cr) in concentrations ranging from 0.02 to 20 mg L−1 applied for 24 h were assessed in Lemna minor and Lemna gibba by measuring changes in protein concentration, ascorbic acid, phenolics, malondialdehyde (MDA), hydrogen peroxide (H2O2), the activity of guaiacol peroxidase (G-POX) and catalase (CAT). Ascorbic acid, phenolics, catalase and guaiacol peroxidase played a key role in the antioxidative response of L. gibba. Inadequate activity of antioxidant enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…An increased concentration of AA was also observed by Zengin and Munzuroglu in Phaseolus vulgaris exposed to lower concentrations of Hg. However, other studies have demonstrated that exposure to higher concentrations of Hg decreased the amount of AA and ASH in Lemna minor , L. gibba , and Triticum vulgare plant tissues . The results provide evidence that L. sativum L. shoots were able to reduce oxidative stress caused by intense production of AA, especially at high Hg concentrations.…”
Section: Resultsmentioning
confidence: 51%
“…An increased concentration of AA was also observed by Zengin and Munzuroglu in Phaseolus vulgaris exposed to lower concentrations of Hg. However, other studies have demonstrated that exposure to higher concentrations of Hg decreased the amount of AA and ASH in Lemna minor , L. gibba , and Triticum vulgare plant tissues . The results provide evidence that L. sativum L. shoots were able to reduce oxidative stress caused by intense production of AA, especially at high Hg concentrations.…”
Section: Resultsmentioning
confidence: 51%
“…As a result of the induced oxidative stress, their exposure to Zn and Cd metals has led to a decline in the protein concentration [19,20]. In Lemna species ascorbic acid, phenolics, catalase and guaiacol peroxidase have been found to play important roles in heavy metal detoxification processes [21]. Cd accumulation has led to an increase in H 2 O 2 and O 2 concentration and in the lipid peroxidation in the leaves of S. natans too.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are similar to the changes in soluble protein content in L. minor reported under treatments with between 0 and 500 μM CdCl 2 (Razinger et al, 2008 ). However, Varga et al ( 2013 ) have reported direct reduction of protein content in L. minor and L. gibba after 24 h exposure to different Hg and Cd concentrations (0, 100, 200, 300, 400, 500, and 600 μM), most likely due to excessive stress in the short-term. The inability to synthesize protein at high Hg concentrations (2, 4, 8 mg/L) might be due to several reasons, such as shortage of energy, carbohydrates or a reduced level of nutrients essential for protein synthesis, such as Mg and K (Mazhoudi et al, 1997 ; Gardea-Torresdey et al, 2004 ; Wang et al, 2008 ), increased protease activity (Palma et al, 2002 ) or structural changes induced by DNA damages or damage to the photosynthetic system (Ates et al, 2004 ; Gardea-Torresdey et al, 2004 ).…”
Section: Discussionmentioning
confidence: 98%
“…A range of protective substances, including antioxidant enzymes (SOD, CAT, POD), soluble proteins, flavonoids, and other phenolics have been shown to accumulate in plants as an adaptive mechanism for coping with certain stresses (Horling et al, 2003 ; Mittler et al, 2004 ; Sharma and Dietz, 2009 ; Varga et al, 2013 ). Each enzyme has a different role to play in plant protection; SOD converts superoxide to H 2 O 2 (Mishra et al, 2006 ), whilst CAT and POD breakdown the H 2 O 2 (Scandalios et al, 1994 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation